2005
DOI: 10.1128/iai.73.4.2400-2410.2005
|View full text |Cite
|
Sign up to set email alerts
|

The UspA2 Protein of Moraxella catarrhalis Is Directly Involved in the Expression of Serum Resistance

Abstract: Many strains of Moraxella catarrhalis are resistant to the bactericidal activity of normal human serum. Previous studies have shown that mutations involving the insertion of an antibiotic resistance cartridge into the M. catarrhalis uspA2 gene resulted in the conversion of a serum-resistant strain to a serum-sensitive phenotype. In the present study, the deletion of the entire uspA2 gene from the serum-resistant M. catarrhalis strain O35E resulted in a serum-sensitive phenotype and did not affect either the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 61 publications
1
73
0
Order By: Relevance
“…However, it is conceivable that uspA2 expression in the serosensitive isolates is below the threshold required to become functionally relevant or may even be completely abolished. In addition, Attia et al have demonstrated that serum resistance is linked to UspA2, but it is not an inherited property of all UspA2 variants (11). The gene coding for the multifunctional Hag protein was found to be absent in almost all isolates belonging to 16S rRNA types 2/3 (17 out of 18), whereas hag was detected in almost all (175 out of 176) 16S rRNA type 1 isolates (150).…”
Section: M35 Porinmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is conceivable that uspA2 expression in the serosensitive isolates is below the threshold required to become functionally relevant or may even be completely abolished. In addition, Attia et al have demonstrated that serum resistance is linked to UspA2, but it is not an inherited property of all UspA2 variants (11). The gene coding for the multifunctional Hag protein was found to be absent in almost all isolates belonging to 16S rRNA types 2/3 (17 out of 18), whereas hag was detected in almost all (175 out of 176) 16S rRNA type 1 isolates (150).…”
Section: M35 Porinmentioning
confidence: 99%
“…The multifunctional aspects of M. catarrhalis UspA proteins are illustrated by their roles in adhesion, invasion, and protection against the human complement system. The role of UspA proteins in serum resistance has been described by several authors (2,11,12,16,147). UspA2 is capable of binding several complement proteins: the C4-binding protein (C4bp) (106), C3 (107), and vitronectin (12,92).…”
Section: Complement Resistance and Major Ompsmentioning
confidence: 99%
“…The UspA2 protein is a putative autotransporter macromolecule that forms relatively short, filamentous projections on the surface of M. catarrhalis cells and is a target for biologically active antibodies [6,37]. In contrast to UspA1, it is not functioning as adhesin but is directly involved in the expression of serum resistance found in UspA2-positive Moraxella strains [5,38,39]. In addition, the results of the present study suggest that the UspA2-mediated activation of PKC controlling the NF-kB-dependent IL-8 release may represent a new virulence mechanism of Moraxella UspA2 in respiratory epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Serum bactericidal survival testing of M. catarrhalis isolates 3.9, 3.18, and their isogenic ⌬ompJ2 mutants was based on a protocol described by Attia et al (1). Briefly, bacterial cultures were grown to mid-log phase (approximately 5 ϫ 10 8 CFU/ml) in MH broth and diluted 1/1,000 in Veronal-buffered saline containing 0.1% (wt/vol) gelatin.…”
Section: Methodsmentioning
confidence: 99%
“…Of particular importance is the UspA2 protein, a vitronectin binding protein whose N-terminal half may confer complement resistance on certain isolates (1,33,41). Other OMPs associated with virulence include the iron acquisition protein CopB (20), a hemagglutinin (28), and the lipooligosaccharide (44).…”
mentioning
confidence: 99%